Towards control of viscous effects in acrylic-based actuator applications. (11th August 2016) - Thylander, S; Menzel, A; Ristinmaa, M
Abstract: Dielectric elastomers offer clear advantages over more traditional and conventional materials when soft, lightweight, noiseless actuator applications with large deformations are considered. However, the viscous time-dependent behaviour associated with most elastomers limit the number of possible applications. For this purpose, the possibility of controlling the viscous response by regulating the applied electric potential is explored. The constitutive model chosen is calibrated to fit the electro-viscoelastic response of an acrylic elastomer often used in dielectric elastomer actuators. The response of both homogeneous deformation examples and inhomogeneous finite element boundary value problems, chosen to mimic existing applications, are presented. Control of both force and displacement quantities are successfully achieved.